Self management of arthritis in primary care: randomised controlled trial. Issue 7574 (13th October 2006) - Buszewicz, Marta; Rait, Greta; Griffin, Mark; Nazareth, Irwin; Patel, Anita; Atkinson, Angela; Barlow, Julie; Haines, Andy
Abstract: Objective To evaluate clinical effectiveness of a self management programme for arthritis in patients in primary care with osteoarthritis. Design Randomised controlled trial. Setting 74 general practices in the United Kingdom. Participants 812 patients aged 50 and over with osteoarthritis of hips or knees (or both) and pain or disability (or both). Intervention Participants were randomised to six sessions of self management of arthritis and an education booklet (intervention group) or the education booklet alone (control group). Main outcome measures Primary outcome was quality of life, as assessed by the short form health survey (SF-36). Several other physical and psychosocial secondary outcomes were assessed. Data were collected at baseline, four months, and 12 months. Results Response rates were 80% and 76% at four and 12 months. The two groups showed significant differences at 12 months on the anxiety subscore of the hospital anxiety and depression scale (mean difference −0.62, 95% confidence interval −1.08 to −0.16), arthritis self efficacy scale for pain (0.98, 0.07 to 1.89), and self efficacy for other aspects of management (1.58, 0.25 to 2.90). Results were similar for intention to treat and per protocol analyses. No significant difference was seen in number of visits to the general practitioner at 12 months. Conclusions The self management of arthritis programme reduced anxiety and improved participants' perceived self efficacy to manage symptoms, but it had no significant effect on pain, physical functioning, or contact with primary care. Trial registration Current Controlled Trials ISRCTN79115352 [controlled-trials.com] .